Iranian Medical Practitioner’s Mental Health - Naghizadeh, Pegah; Aliakbari, Fereshteh; Hashemi, Reza; Ranjgar, Bayramali (Archives of Men's Health, 2020)
Introduction: While the Mental health of Medical practitioners has drawn much attention worldwide in recent years, it has been neglected in Iran. This research aims to provide a quick insight into the mental health of the medical practitioner. Methods: Samples were 208 medical practitioners with different scientific ranks and various specialties in an educational hospital in Tehran. The General health questionnaire (GHQ-12) was used as research too. Results: The Data collected by standard GHQ-12 questionnaire and demographic survey were analysed with a cut-off point of 3 for classifying GHQ status among medical practitioners and3.5 (average point of Iranian adults according to Ebadi et al. 2006) for comparing medical practitioners with the general population. Data analysis revealed that 51.4% of medical practitioners fell below the average point of Iranian society in terms of mental health. Other criteria were gender, marital status, scientific rank, work experience, and specialty. There was no significant difference between males and females (Z=-1.662, p<0.096) and between single and married ones (Z=0.604, p<0.546). A significant difference existed between medical practitioners with different scientific ranks (assistant, assistant professor, associate professor, and professor) (Z=7.614, p<0.022). There was also a significant positive relationship between work experience and mental health (r=0.240, p<0.001) and between age and mental health (r=0.201, p<0.004). A comparison of surgical groups with the non-surgical group confirmed the absence of significant difference (Z=-1.252, p<0.210), with both groups suffering from equally poor mental health. The average mental health of internists and pathologists was significantly lower than general surgeons and physiologists. Conclusion: The results denote that medical practitioners are exposed to stressful events arising from their profession. It is recommended that their occupational conditions be carefully examined, and mental health promotion programs are designed and implemented.